P77 Carcinoma In-situ At The Bronchial Resection Margin – A Case For Routine Surveillance With Autofluorescence Bronchoscopy. (10th November 2014) - Thakrar, RM; Brown, JM; Apperley, H; Falzon, M; Lawrence, DR; George, PJ; Navani, N; Janes, SM
Abstract : Introduction: Lung cancer is the leading cause of cancer mortality worldwide, with squamous cell carcinomas commonly arising in the central airways and accounting for nearly 30% of cases. Progression from normal bronchial epithelium to carcinoma in-situ (CIS) has been well described, and is found at the resection margin after lobectomy in up to 2.5% of cases; however, its fate has not been defined. Method: Cases referred to the autofluoresence bronchoscopy (AFB) surveillance programme at this institution were analysed retrospectively from 1999–2012, for all those shown to have CIS at the resection margin following surgery for TxN0M0 squamous cell carcinoma. Patients underwent longitudinal assessment of the tracheobronchial tree to (a) confirm CIS at the resection margin and track its fate over time (b) characterise development of other preinvasive lesions. Results: Twenty-two cases were identified with a median interval of 6 months (range 3–9) from surgical resection to first AFB. Thirteen patients (59%) were confirmed to have CIS on biopsy at the bronchial resection margin during the first AFB. Eleven (85%) of these progressed to invasion over a median interval of 37 months (range 4–85). A subgroup of these (5 patients) developed 8 invasive cancers at sites distant to the anastomotic site and 9 patients had >1 CIS lesion at a distant site. Two patients (9%) found to have CIS after initial post-resection AFB, persisted after follow-up of 36–45months. Although no progression has been seen, both have developed CIS at distant sites to the resection margin. Nine patients (41%) were found to have no evidence of CIS at the resection margin and during a median surveillance period of 37 months (range 19–126), all were found to have normal bronchial epithelium. One patient in this group developed a second primary lung cancer that was surgically resected. Conclusion: CIS at the bronchial resection margin is a strong indicator of its fate to progression to invasive carcinoma. Its persistence sets precedent for the development of multiple, consecutive CIS lesions and invasive squamous cell carcinomas, and highlights the importance of routine AFB surveillance following surgery in these cases.